Beyond Advertising - Yoram ( jerry) Wind (Wiley, 2016)
The fundamental relationships among brands, media, and people are being transformed, and just as we try to adapt, along comes a new disruption. Are you and your organization prepared to deal with today's unprecedented speed and scope of technological change? Beyond Advertising provides a business transformation road map for an aspirational future, based on the insights of more than 200 of the world's most forward-thinking executives, innovators, and academics all grappling with today's unique challenges and opportunities.